Marital power and depressive symptoms among older Mexican adults. Issue 11 (27th June 2018) - Saenz, Joseph L.; Rote, Sunshine
Abstract: An extensive body of research documents marital status differences in health among older adults. However, few studies have investigated the heterogeneity in depressive symptomatology among older married adults living in developing countries. Our study investigates the interplay of gender and marital power dynamics for mental health among older Mexican adults. Our sample includes older married couples in the 2015 Wave of the Mexican Health and Aging Study (N = 3, 621 dyads). We use seemingly unrelated regression to model the association between self-reported distributions of decision-making power within marriages and depressive symptoms for husbands and wives. For approximately 41 per cent of couples, the husband and wife both reported an equal distribution of power in the marriage. Compared to those who reported an equal power distribution, husbands and wives who reported an imbalance of power (having more power or less power than their spouse) reported more depressive symptoms. Levels of depressive symptoms were higher in marriages characterised by power inequality. The relationship between equality in power and depressive symptoms is not explained by health-care needs or living arrangements. Marital quality is an important factor for understanding depressive symptoms among older Mexican adults.